Hallazgo de un nido de Chorlito de Vincha (Phegornis mitchelli) en Mendoza, Argentina - Fernandes d’Oliveira, Gustavo (1997)
We describe a nest with eggs of Phegornis mitehelli found at 2850 m in the Andes of Mendoza Province. It is the first nest of the species described for Argentina.